TREATMENT TO HANDLING SYMPTOMS BURDEN ON GYNECOLOGICAL CANCER PROBLEMS: LITERATURE REVIEW - Nunung Nurhayati; Dewi Marfuah; Astri Mutiar (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2021)
Gynecological cancer is one of the most common reproductive health problems. The morbodity and mortality rates of women with gynecologic cancer were increasing. Women with gynecologic cancer have symptoms burden over time. Treatment are needed to support patients in the adaptation process and maintain a balance of well-being while symptoms occur. This article used a literature review with the narrative review method. The article searched were performed on databased PubMed and Google Scholar with the keywords symptoms burden AND management OR intervention. Studies published from 2010 to 2020 are considered for inclusion in this review and using Indonesian and English. Assessment of study quality is carried out in accordance with JBI's critical appraisal and grade recommendation analysis based on EBM. There were 6 articles that matched the criteria, one was a systematic review and the other five had an RCT research design. The results of this review suggest that the most article highlighted psychological symptoms burden. The intervention used to reduce the symptoms burden range from actions that provide a relaxing effect such as reflexology massage, progressive muscle relaxation, cognitive behavioral therapy, and mindfulness-based therapy. And there are interventions that focus on developing self-management in handling symptoms such as guided self-determination, psychoeducation and leadership and coaching for health. Thus, nursing care is recommended to be able to make these various intervention happen consistently and developed according to patient needs.